Public Service Provision, User Fees and Political Turmoil. - Fafchamps, M; Minten, B (Oxford University Press, 2007)
This study looks at public service delivery in rural areas of Madagascar. The blockade of the central highlands of Madagascar by a defeated president let us examine the short-term effect of a large unanticipated macro shock and subsequent elimination of user fees on the rural delivery of health and education services. We found enrolment in rural primary schools surprisingly resilient to the crisis, probably because it unfolded in the middle of the school year. In contrast, the blockade led to a large drop in health care services, measured by the number of patient visits to health care centres. Part of this effect can be explained by an increase in monetary poverty. After the blockade, user fees were suspended in schools and health centres but the measure was not applied immediately in all rural communes. Controlling for supply effects, time dummies and school and health centre fixed effects, we find that the suspension of user fees is associated with a significant increase in both school enrolment and visits to health centres.